Using memes in Portuguese classes: a look over the pedagogical innovating practices in the Languages and Codes area - Lopes, Luiz Fernando de Oliveira; Almeida, Alisandra Cavalcante Fernandes de (Educação, Escola & Sociedade, 2020)
The research investigates the contributions arising from the use of memes as a didactic-pedagogical tool in Portuguese classes. The analysis brings subsidies to the current literature, at the core of collaborative and innovative practices, by addressing the use of this discursive genre in the classroom. To carry out the qualitative research, the data were collected through the offering of a workshop resulting in the observations, questionnaire and interview. Participants in the survey were third-year high school students from a school located in Ceará, Brazil. As results, the study presents new alternatives to intervene in the classroom, taking into account the possibilities of improving collaboration among peers, dialogue, creativity, use of digital resources, oratory and optimized view of the Portuguese content, in addition to understanding the error as an integral part of learning. Therefore, it is perceived that innovative interventions in the classroom are substantial in the composition of school curricula.